The Effect Of High-Intensity Exercise Training On Serum Calcium Of Female Combat Athletes - Seyed Mohammad Hoseini Ravesh; Masha Nakhaei Moghadam (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2023)
Purpose: Cell homeostasis is an essential factor in maintaining cellular health and intracellular mechanisms, which can also be associated with inflammatory factors and increased stress for muscle cell health. Calcium is also a necessary factor in cell health and is to establish homeostasis in the body. This study aimed to investigate the effect of high-intensity training on serum calcium levels in combat women. Method: For this purpose, 18 women karateka in the age range of 17 to 23 years were randomly divided into 2 groups: control (n=7) and exercise ((n=11). The exercise group performed proper exercises to improve karate and aerobic techniques for 6 weeks in the intensities of more than 80% of the maximum heart rate reserve. Physiological indices and blood samples were measured 24 hours before and 48 hours after the training protocol. To measure calcium cell biomarker, the Pars Azmoon calcium kit was used. Research data were analysed by covariance test at the significant level (P≤0.05) using SPSS software version 25. Results: After six weeks of high-intensity training, there was a significant difference in serum calcium levels in the exercise group compared to the control group (P = 0.002). Also, the results within the group showed a significant increase in serum calcium (P = 0.016) in the exercise group compared to baseline conditions. Conclusions: High intensity training seems to increase serum calcium in female athletes, and this can lead to precursors to cellular disorders, muscle damage and increase inflammatory factors and ultimately decrease the performance of female athletes. However, more research is essential in this regard.